Islam in Pakistan : A History - Zaman, Muhammad Qasim (Book collections on Project MUSE., 2018)
"The first modern state to be founded in the name of Islam, Pakistan was the largest Muslim country in the world at the time of its establishment in 1947. Today it is the second-most populous, after Indonesia. Islam in Pakistan is the first comprehensive book to explore Islam's evolution in this region over the past century and a half, from the British colonial era to the present day. Muhammad Qasim Zaman presents a rich historical account of this major Muslim nation, insights into the rise and gradual decline of Islamic modernist thought in the South Asian region, and an understanding of how Islam has fared in the contemporary world. Much attention has been given to Pakistan's role in sustaining the Afghan struggle against the Soviet occupation in the 1980s, in the growth of the Taliban in the 1990s, and in the War on Terror after 9/11. But as Zaman shows, the nation's significance in matters relating to Islam has much deeper roots. Since the late nineteenth century, South Asia has witnessed important initiatives toward rethinking core Islamic texts and traditions in the interest of their compatibility with the imperatives of modern life. Traditionalist scholars and their institutions, too, have had a prominent presence in the region, as have Islamism and Sufism. Pakistan did not merely inherit these and other aspects of Islam. Rather, it has been and remains a site of intense contestation over Islam's public place, meaning, and interpretation. Examining how facets of Islam have been pivotal in Pakistani history, Islam in Pakistan offers sweeping perspectives on what constitutes an Islamic state."--Provided by publisher